KEKERASAN TERHADAP PEREMPUAN DALAM TEKS NOVEL BANATU‘R-RIYADH KARYA RAJA‘ ASH-SHANI‘I:KAJIAN FEMINIS PSIKOANALISIS - Yeni Puspitasari, Eva Farhah (Center of Middle Eastern Studies (CMES): Jurnal Studi Timur Tengah, 2016)
This research discuss about the forms of violence against woman in Banatu‘r-Riyadh novel by Raja Ash-Shani‘i based on Feminist Literary Criticism of Psychoanalysis theory by Helen Cixous. Therefore, the purpose of this research are to describe forms of violence against woman based on Feminist Literary Criticism of Psychoanalysis theory by Helen Cixous. The research findings are 1) The Domestic violence: the physical violence and the emotional violence, 2) the public violence with the emotional violence.